PENGARUH PEMBINAAN DAN DISIPLIN GURU OLAHRAGA TERHADAP PENGEMBANGAN EKSTRAKURIKULER BOLA VOLI - Hadi Kosasih, Alam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2017)
The research entitled The Influence of Coaching And Discipline of Teacher Exercise on Vitar Ball Extracurricular Development is aimed to find out whether there is an influence between "Development and discipline of Sports Teachers towards Vocational Ball Extracurricular Development in SMP Negeri 2 Jatinangor Sumedang Regency." The research conducted is quantitative research. The sample used amounted to 30 people. Determination of sample using random sampling technique. Prior to data analysis, normality and homogeneity tests were first conducted to determine whether the data showed normal and homogeneous. Data analysis technique used is f-test. From the calculation of regression analysis X1 and X2 to Y in the regression coefficient value of Fcount = 6.37> Ftable = 4.21 can be concluded that H0 rejected and Ha accepted, thus in penelitin conducted there is a significant influence between Development and Teacher Discipline against Development of Extracurricular Voly Ball at SMP Negeri 2 Jatinangaor Sumedang District.